2014
DOI: 10.1016/j.molcel.2014.04.031
|View full text |Cite
|
Sign up to set email alerts
|

NCOA4 Transcriptional Coactivator Inhibits Activation of DNA Replication Origins

Abstract: NCOA4 is a transcriptional coactivator of nuclear hormone receptors that undergoes gene rearrangement in human cancer. By combining studies in Xenopus laevis egg extracts and mouse embryonic fibroblasts (MEFs), we show here that NCOA4 is a minichromosome maintenance 7 (MCM7)-interacting protein that is able to control DNA replication. Depletion-reconstitution experiments in Xenopus laevis egg extracts indicate that NCOA4 acts as an inhibitor of DNA replication origin activation by regulating CMG (CDC45/MCM2-7/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 52 publications
1
54
0
Order By: Relevance
“…For this purpose, we incubated extracts sequentially with digoxigenin-dUTP and biotin-16-dUTP, prepared DNA fibers from nuclear fractions, and then measured inter-origin distances (Bellelli et al, 2014; Marheineke et al, 2009). We observed that the WT TRCT fragment caused a significant increase in shorter inter-origin distances (e.g., 10–15 kb) relative to incubations containing added buffer alone or the 7A fragment (Figure 6C; Figures S6A and S6B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we incubated extracts sequentially with digoxigenin-dUTP and biotin-16-dUTP, prepared DNA fibers from nuclear fractions, and then measured inter-origin distances (Bellelli et al, 2014; Marheineke et al, 2009). We observed that the WT TRCT fragment caused a significant increase in shorter inter-origin distances (e.g., 10–15 kb) relative to incubations containing added buffer alone or the 7A fragment (Figure 6C; Figures S6A and S6B).…”
Section: Resultsmentioning
confidence: 99%
“…Labeled DNA fibers were prepared as described (Bellelli et al, 2014; Marheineke et al, 2009). Human U2OS cells were labeled with 40 μM CldU, washed with phosphate-buffered saline (PBS), and finally labeled with 50 μM IdU as indicated in figures.…”
Section: Methodsmentioning
confidence: 99%
“…All primers were from (27), except c-MYC (46) and PTGS2, NETO1 and SLITRK6 (47). All primers were used at a final concentration of 400 nM.…”
Section: Methodsmentioning
confidence: 99%
“…Reduction of NCOA4 protein hindered co-localization of FTH1 with LC3B/LAMP1; furthermore, NCOA4 reduces IRP-2 and CD71 protein (Mancias et al, 2014). Functions independent of ferritinophagy include NCOA4’s ability to regulate DNA replication via binding to MCM7; further, deficiency of NCOA4 activates DNA replication origin activation via CMG helicase regulation (Bellelli et al, 2014). Additionally, NCOA4 mediates DNA damage/replication stress events (i.e., fork stalling, inhibition of fork speed, and premature senescence) (Bellelli et al, 2014).…”
Section: Dysregulation Of Iron Metabolism In Cancermentioning
confidence: 99%